Legal Certainty For Workers Due To Company Takeover (Acquisition) - Indradjaja, Nobella; Chamdani, Chamdani (Journal of Law, Politic and Humanities, 2024)
Limited Liability Companies (LLCs) are crucial for driving and directing economic progress. Limited liability companies are crucial in driving and driving economic progress, particularly in the middle of globalization and liberalization of the increasingly complicated global economy. A company takeover is a legal action designed to increase a firm's viability and effectiveness by purchasing or disposing of shares of the target company. The law governing the selling and acquisition of shares that transfer rights are the main topic of this study. The research method used in writing this scientific paper was a normative research method with an analytical and conceptual approach which is carried out by analyzing legal concepts related to the legal issues faced. It is crucial to pay close attention to whether buying and selling shares in the legal transaction results in a change of ownership. The position of employees of the company whose shares were purchased does not, however, immediately end as a result of the transfer of rights to the company, unless there is an extra agreement in the company transfer agreement